2014
DOI: 10.1111/mmi.12592
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine stabilizes Cdc25 independently of Rad3 in Schizosaccharomyces pombe contributing to checkpoint override

Abstract: Cdc25 is required for Cdc2 dephosphorylation and is thus essential for cell cycle progression. Checkpoint activation requires dual inhibition of Cdc25 and Cdc2 in a Rad3-dependent manner. Caffeine is believed to override activation of the replication and DNA damage checkpoints by inhibiting Rad3-related proteins in both S chizosaccharomyces pombe and mammalian cells. In this study, we have investigated the impact of caffeine on Cdc25 stability, cell cycle progression and checkpoint override. Caffeine induced C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(65 citation statements)
references
References 70 publications
4
61
0
Order By: Relevance
“…We previously demonstrated that caffeine stabilises both wild type (wt) Cdc25-GFP int and the Cdc25 (9A) -GFP int mutant that lacks 9 major inhibitory phosphorylation sites and is normally degraded following exposure to genotoxic agents (Frazer & Young, 2011, Frazer & Young, 2012, Alao et al, 2014. In this study, exposure to 10 mM caffeine also stabilised the Cdc25 (12A) mutant protein that lacks all 12 inhibitory phosphorylation sites ( Fig.…”
Section: Caffeine Stabilises Cdc25 By Inhibiting Its Nuclear Degradationmentioning
confidence: 50%
See 4 more Smart Citations
“…We previously demonstrated that caffeine stabilises both wild type (wt) Cdc25-GFP int and the Cdc25 (9A) -GFP int mutant that lacks 9 major inhibitory phosphorylation sites and is normally degraded following exposure to genotoxic agents (Frazer & Young, 2011, Frazer & Young, 2012, Alao et al, 2014. In this study, exposure to 10 mM caffeine also stabilised the Cdc25 (12A) mutant protein that lacks all 12 inhibitory phosphorylation sites ( Fig.…”
Section: Caffeine Stabilises Cdc25 By Inhibiting Its Nuclear Degradationmentioning
confidence: 50%
“…Mik1 is required for maintenance of the replication damage checkpoint signalling in S. pombe mutants expressing Cdc25 (12A) -GFP int (Frazer & Young, 2011, Frazer & Young, 2012. As observed for rad3Δ and cds1Δ mutants (Alao et al, 2014), Cdc25 appeared more stable in a mik1Δ genetic background ( Fig. 1 A).…”
Section: Caffeine Stabilises Cdc25 By Inhibiting Its Nuclear Degradationmentioning
confidence: 56%
See 3 more Smart Citations